The Effect of Interactive Learning Media Based on GlideApps on Students’ Digital Literacy in Informatics Subjects - Anisa Permata Sari; Silfia Hasanah; Wahyudin; Munir; Galih Yudha Saputra (Poltanesa, 2025)
The rapid development of digital technology requires the improvement of students’ digital literacy, particularly in Informatics education. Digital literacy goes beyond the ability to operate technological devices, encompassing critical thinking, collaboration, and understanding of digital ethics. To support these competencies, interactive learning media relevant to students’ digital context are essential. GlideApps, a no-code web-based application platform, provides an innovative solution that enables teachers and students to independently develop interactive learning media. This study aims to analyze the role of GlideApps in enhancing students’ digital literacy in Informatics subjects. The research employs a Systematic Literature Review (SLR) of national and international studies published between 2018 and 2024. The findings reveal that GlideApps promotes student engagement, supports project-based learning, and simplifies application development without requiring programming skills. Moreover, it fosters students’ understanding of computational thinking and the ethical use of digital technology. However, challenges remain, including limited teacher training, unequal infrastructure, and the scarcity of specific research on GlideApps’ impact on digital literacy dimensions. The study concludes that GlideApps holds significant potential as an interactive learning medium to strengthen digital literacy, while recommending further context-based and in-depth research.